Myiasis in humans and other animals, including applied applications in larval therapy & forensic entomology - Stevens, Jamie (Henry Stewart Talks, 2010)
Typical larval infestations, The importance of myiasis-causing flies, Defining myiasis, Classification of myiasis, Blowflies and screwworm flies, Comparison of blowfly lifecycles, Economic impact of myiasis, Furuncular & Sanguinivorous larvae, Flesh flies: Sarcophagidae, Bot and warble flies: Oestridae, Other flies and the rat-tailed maggot, Evolution of parasitism in myiasis-causing flies & of myiasis, Breeding strategies influencing myiasis control, Myiasis control: traps, targets and insecticides, Disease ecology, Distribution of New World screwworm fly, SIT programme in North and Central America, Climate data, models and control, Larval therapy
Updated at 2021/05/31